2020
DOI: 10.3390/plants9030373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rhizome Integration on the Water Physiology of Phyllostachys edulis Clones Under Heterogeneous Water Stress

Abstract: Water is crucial to plant growth and development. Under heterogeneous environmental water deficiency, physiological integration of the rhizomatous clonal plant triggers a series of physiological cascades, which induces both signaling and physiological responses. It is known that the rhizome of Phyllostachys edulis, which connects associated clonal ramets, has important significance in this physiological integration. This significance is attributed to the sharing of water and nutrients in the vascular bundle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…The excess H 2 O 2 produced in salt response was decomposed into O 2 and H 2 O under the catalysis of CAT and POD (Schuller et al, 1996). Physiological integration significantly contributed to the decrease in MDA and H 2 O 2 contents in salt‐stressed ramets, which was in agreement with previous studies (Jing et al, 2020; Wei et al, 2019). Jing et al (2020) indicated that physiological integration improved the ability of ROS scavenging by changing of metabolism of CAT and POD, which were weaker in water‐stressed ramet and stronger in normally watered ramet.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The excess H 2 O 2 produced in salt response was decomposed into O 2 and H 2 O under the catalysis of CAT and POD (Schuller et al, 1996). Physiological integration significantly contributed to the decrease in MDA and H 2 O 2 contents in salt‐stressed ramets, which was in agreement with previous studies (Jing et al, 2020; Wei et al, 2019). Jing et al (2020) indicated that physiological integration improved the ability of ROS scavenging by changing of metabolism of CAT and POD, which were weaker in water‐stressed ramet and stronger in normally watered ramet.…”
Section: Discussionsupporting
confidence: 92%
“…Physiological integration significantly contributed to the decrease in MDA and H 2 O 2 contents in salt‐stressed ramets, which was in agreement with previous studies (Jing et al, 2020; Wei et al, 2019). Jing et al (2020) indicated that physiological integration improved the ability of ROS scavenging by changing of metabolism of CAT and POD, which were weaker in water‐stressed ramet and stronger in normally watered ramet. Differently, we measured equal induction of POD and CAT (including the enzymes activity and the expression of their encoding genes) in stolon connected and severed regimes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Clonal plants produce their offspring via not only sexual reproduction but also asexual reproduction, in which new individual clones with an identical gene set, called ramets, are generated [ 1 , 2 , 3 , 4 , 5 , 6 ]. Elucidating the mechanism by which clones forage resources in heterogeneous environments is a central issue in clonal plant ecology [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], plant growth modeling [ 23 ], and their application in vegetation management [ 17 , 18 , 19 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Additionally, the spatial arrangement of ramets determines the reproductive success of clonal plants; this is because aggregation of ramets that belong to the same genets leads to an increased percentage of geitonogamous self-pollination [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with studies in laboratories or gardens, studies on resource foraging of wild plants in their natural habitats (e.g., [ 12 , 38 , 41 ]) are limited. Moreover, most of the previous studies on resource foraging of clonal plants have investigated herbaceous [ 7 , 8 , 9 , 10 , 11 , 12 , 16 , 17 , 18 , 19 , 20 , 24 , 38 , 40 , 41 , 42 , 44 , 46 , 47 ] or bamboo [ 13 , 15 ] species. The reproductive biology [ 1 , 29 , 55 , 56 , 57 , 58 , 59 ] and resultant genetic structure of populations [ 60 , 61 , 62 ] of clonal woody species have been studied intensively.…”
Section: Introductionmentioning
confidence: 99%